EXPLORING LEARNING OBSTACLES OF SENIOR HIGH SCHOOL STUDENTS IN GREEN CHEMISTRY ON THE TOPIC OF BIODEGRADABLE PLASTIC - Azizah, Naila; Supriatna, Asep; Hernani, Hernani (JURNAL EDUSCIENCE, 2025)
Purpose – This research aims to identify the learning obstacles experienced by senior high school students in studying green chemistry.Methodology – This study used a qualitative descriptive design with a learning obstacle analysis approach. Data were collected through in-depth interviews with students at a senior high school in Indonesia. The interview guideline covered several themes, including student learning experiences, conceptual understanding, learning methods, and the obstacles that students faced in applying green chemistry to everyday life. The collected data was then analyzed and categorized to identify any obstacles encountered.Findings – The results indicate that students' primary obstacles are epistemological, including limited prior knowledge, a superficial understanding of Green Chemistry principles, and difficulties in applying these concepts to real-life contexts. Students rarely experience project-based learning and mainly rely on rote learning and repeated explanations from teachers, which do not fully resolve their conceptual gaps.Contribution – This study highlights the use of lesson design that provides more interactive and contextual learning, helping students connect chemistry learning in green chemistry with everyday practices. This research also provides insights for teachers in designing effective learning by anticipating students' learning obstacles, thereby supporting the realization of sustainable chemistry education.